THE EXPERIMENTAL STUDY OF NOTE TAKING PAIRS IN TEACHING READING (Case Study in STAIN Pekalongan in the 2013/2014 Academic Year) - Marlina (JURNAL PENELITIAN, 2015)
This research is intended to know whether: (1) Note Taking Pairs is more effective than Direct Instructional Method to teach reading; (2) Students who have high interest have better reading skill than students who have low interest; and (3) There is an interaction between teaching methods and students’ interest in teaching reading. The method which was applied in this research was Experimental study. It was conducted at STAIN Pekalongan in the 2013/2014 Academic Year. The population was the English 3 Students of STAIN Pekalongan in the 2013/2014 Academic Year. It consists of four classes (128 students). The writer used cluster random sampling to get the sample. It consists of two classes: (1) 32 students of A class, and (2) 32 students of B class. The data analysis shows the following findings : (1) Note Taking Pairs is more effective than Direct Instructional Method for teaching reading to the English 3 students of STAIN Pekalongan in the 2013/2014 academic year; (2) The students who have high interest have better reading skill than the students who have low interest of the English 3 students of STAIN Pekalongan in the 2013/2014 academic year; and (3) There is an interaction between teaching methods and students’ interest in teaching reading to the English 3 students of STAIN Pekalongan in the 2013/2014 academic year.Hopefully, the result of this research will be useful for lecturers in order to choose and determine the suitable teaching method used in their class.